Approaching Conceptual Blending in the Holy Qur'an - A Cognitive Semantic Study- - Dr. Nyan Othman Sharif,; Dr. Majid Hamid Awkhti, (Journal of College of Education, 2025)
Cognitive linguistics is the science that studies the mental aspect of language, as an aspect independent of other cognitive studies. Conceptual blending theory is a branch of cognitive theory that builds on its tools and uses its ideas. This theory arose from the question of how new concepts are created in human thought, including images, ideas, actions, and formulations in all fields, through a cognitive (inner) background. The resulting actions, at the conscious level, appear simple and straightforward, but are in fact the product of a number of extremely complex laws. This is what is called the conceptual blending network. Applying this theory to texts, especially the Qur'an, inspires insights into how to blend spaces and ideas in Qur'anic expression to understand the text as intended.
Keywords: Cognitive linguistics, Conceptual blending theory, mental, conceptual blending network.